Epidemiological features of the leprosy transmission in relation to armadillo exposure - Deps, Patrícia Duarte (2003)
Introduction and purpose: Some authors demonstrated the possibility of the armadillos, Dasypus novemcinctus, being an environmental source of Mycobacterium leprae. An epidemiologic survey was done to check the correlation between the human contact with armadillos and the incidenceof leprosy. It discusses some features that could be involved in the dynamic process of the leprosy development. The objective of this research is to check the frequency of cases of leprosy contacts with armadillos and also the interhuman contact before their diagnosis to establish the possibility of the M. leprae transmission to the human being through the contact with armadillos. Methods: One hundred and seven leprosy patients were surveyed (leprosy patients that had finished the MDT treatment) who lived in the Pedro Fontes Colony-Hospital, in Cariacica, Espirito Santo State, Brazil, 29 leprosy patients and 173 non leprosy patients from a dermatology service of the city of Vitória, Brazil. The survey included data about the armadillo meat consumption before leprosy diagnosis, the existence of known cases and/or familial leprosy cases. The data were analyzed by Qui-square test, correlation and Exact Fischer Test. Results: 90.4% of the leprosy patients or cured leprosy patients had once eaten armadillo meat before their leprosy diagnosis, while 15% of the non leprosy patients had already eaten armadillo meat. In a group without leprosy contact before the diagnosis, 96,1% ate armadillo meat, and 3,9% didn't eat. This study supposes a possible source of the M. leprae by the armadillo meat consumption, mainly, in a leprosy patients without previous leprosy contact.